Koszty transakcyjne ex ante jako determinanta rozwoju małych elektrowni wodnych na przykładzie województwa łódzkiego - Sołtuniak, Joanna (Gospodarka w Praktyce i Teorii, 2011)
The article highlights the water power engineering potential and its use, including information on development of Small Hydro Power (SHP) plants in Voivodeship of Lodz. The process of investing in SHP as well as associated risk are presented in economic categories in relation to economy of transaction costs. The necessity to simplify administrative procedures was indicated.